Psalm 5 and the polarity between those who may stand before Yahweh and those who may not - Botha, Philippus J. (HTS Theological Studies, 2018)
Psalm 5 is often described as an example of a prayer of someone who has been falsely accused of wrongdoing. Based on the contents of the middle part of the psalm, its wisdom features and especially the parallels it forms with Psalm 1, it is argued in this article that the editors of the Psalter attempted to present the psalm as a prayer of David at the time of his flight from Absalom. In this prayer of the endangered king, he (prophetically) pronounced judgement on the actions and attitudes of his opponents and respectfully entrusted himself to the care of Yahweh. In its literary context, the psalm was therefore probably meant to censure arrogant and irreligious compatriots of the editors, because they exploited fellow Jews, and also to provide hope and encouragement to those exploited members of the in-group.
free